ANALISIS PENGARUH NISBAH BAGI HASIL TERHADAP JUMLAH NASABAH PEMBIAYAAN MUSYARAKAH DI PT. BPRS Bhakti Sumekar Sumenep - Mujibno Mujibno; Ikawati Ikawati (Assyarikah: Journal of Islamic Economic Business, 2022)
The purpose of this study was to determine whether or not there is an influence given by the profit sharing ratio on the number of musharaka financing customers. This research is a quantitative field research (field research) using a simple linear regression test, with a research sample of 36 respondents from several staff at PT. BPRS Bhakti Sumekar using probability sampling method with cluster random sampling type. The instruments and data collection techniques used were questionnaires which were then processed using SPSS software version 20.0. The results of this study indicate the profit-sharing ratio variable with a significance value of 0.000 <0.05, which means that the independent variable has a positive effect on the dependent variable and Tcount (5.343) > from Ttable (2.03452), so it can be concluded partially (t-test) there is a significant positive effect. from the profit-sharing ratio to the number of musyarakah financing customers and based on the results of the coefficient of determination (R2), a value of 0.456 is obtained, which means the effect of the profit-sharing ratio on the number of musyarakah financing customers is 45.6%, while 54.4% is influenced by other factors.